Broiler Poultry Feed Cost Optimization Using Linear Programming Technique. Issue 1 (June 2020) - Mallick, Priyaranjan; Muduli, Kamalakanta; Biswal, Jitendra Narayan; Pumwa, John
Demand for poultry meat and eggs is increasing at a faster pace due to its good quality, nutritive values, and reasonable price. With the growing demand for egg and poultry meat, the demand for poultry feed is also increasing. Most of the feed ingredients which are used in poultry feed are also used for human nutrition. So these major feed ingredients and cumulatively poultry feed are facing market competition with increased cost. This study proposed linear programming (LP) technique to minimize the feed cost for small scale poultry farms. It employs locally available feed ingredients to formulate the broiler starter and finisher feed mix. The dietary nutrient requirement for broiler starter and finisher stage were determined from the prescribed standard specifications by Indian standard institutes and National Research Centers, Indian Council of Agricultural Research (ICAR). Sixteen feed ingredients were selected to formulate the optimal feed mix to minimize the total cost of feed mix subject to the essential nutrient constraints. Microsoft excel solver was used for the formulation of liner programming model and optimal feed mix for broiler starter and finisher were obtained.